Kepedulian Sosial Ibu dalam Mendampingi Anak Berkebutuhan Khusus di Sekolah Luar Biasa Kecamatan Mandau - Lestari, Wulan Suci; Ayub, Daeng; Ramadhani, Masytha (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Children with special needs require sustained family support to facilitate their educational, emotional, social, and adaptive development. However, empirical evidence concerning maternal social care in non-metropolitan special-school settings remains limited, particularly studies that simultaneously examine emotional, instrumental, and cognitive dimensions. This study aimed to describe the level of maternal social care for children with special needs, identify its most dominant dimension, and determine the aspect that still requires strengthening. A descriptive quantitative survey with a cross-sectional design was conducted involving 85 mothers selected through purposive sampling from a population of 107 mothers whose children were enrolled at SLB Cendana Duri and SLB Aisyiyah Duri, Mandau District. Data were collected using a five-point Likert-scale questionnaire and analyzed through descriptive statistics, including frequency, percentage, mean, median, minimum, and maximum scores. The findings showed that the overall level of maternal social care was high, with a mean score of 4.16. A total of 56.47% of respondents were categorized as high, 41.18% as very high, and 2.35% as moderate. Instrumental care obtained the highest mean score (4.17), followed by emotional care (4.16), while cognitive care achieved the lowest mean score (4.10), although it remained within the high category. These results indicate that mothers primarily express social care through direct assistance, daily accompaniment, and involvement in school activities. The relatively lower cognitive dimension highlights the need to strengthen disability literacy, structured parental consultation, and access to reliable information. The study provides local empirical evidence to support the development of school–family partnership programs in special education. Abstrak: Anak berkebutuhan khusus membutuhkan dukungan keluarga yang berkelanjutan untuk menunjang perkembangan pendidikan, emosional, sosial, dan kemandirian. Namun, pemetaan kepedulian sosial ibu pada konteks sekolah luar biasa di wilayah nonmetropolitan masih terbatas, terutama yang mengkaji dimensi emosional, instrumental, dan kognitif secara bersamaan. Penelitian ini bertujuan mendeskripsikan tingkat kepedulian sosial ibu, mengidentifikasi dimensi yang paling dominan, dan menentukan dimensi yang masih memerlukan penguatan. Penelitian menggunakan survei kuantitatif deskriptif dengan pendekatan potong lintang. Sebanyak 85 ibu dipilih secara purposif dari populasi 107 ibu di SLB Cendana Duri dan SLB Aisyiyah Duri. Data dikumpulkan menggunakan kuesioner skala Likert lima poin dan dianalisis melalui frekuensi, persentase, mean, median, nilai minimum, dan maksimum. Hasil penelitian menunjukkan rata-rata kepedulian sosial sebesar 4,16 dan termasuk kategori tinggi. Sebanyak 56,47% responden berada pada kategori tinggi, 41,18% sangat tinggi, dan 2,35% sedang. Dimensi instrumental memperoleh rata-rata tertinggi sebesar 4,17, diikuti dimensi emosional sebesar 4,16 dan dimensi kognitif sebesar 4,10. Temuan menunjukkan bahwa kepedulian ibu terutama diwujudkan melalui tindakan konkret, pendampingan aktivitas harian, dan keterlibatan dalam kegiatan sekolah. Meskipun seluruh dimensi tergolong tinggi, aspek kognitif menjadi prioritas penguatan. Sekolah dan pemerintah daerah perlu mengembangkan kelas orang tua, konsultasi terstruktur, serta akses terhadap informasi yang valid dan mudah dipahami.